METHODS OF TEACHING WALKING TECHNIQUE TO 5-8-YEAR-OLD CHILDREN PARTICIPATING IN FOOTBALL LESSONS - Zokirov Ulugbek Murodjon ogli; Ismailova Xilola Botir qizi (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the methods of teaching walking techniques to 5-8-year-old children participating in football training, the results of practical studies and questionnaires on football training in general secondary schools will be considered.